2010
DOI: 10.1007/s11626-010-9324-0
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of glutamate vesicular transporter (VGLUT1) and choline acetyltransferase (ChAT) proteins in fetal rat hippocampal neurons in culture

Abstract: A very small population of Choline acetyltransferase (ChAT) immunoreactive cells is observed in all layers of the adult hippocampus. This is the intrinsic source of the hippocampal cholinergic innervation, in addition to the well-established septo-hippocampal cholinergic projection. This study aimed at quantifying and identifying the origin of this small population of ChAT-immunoreactive cells in the hippocampus at early developmental stages, by culturing the fetal hippocampal neurons in serum-free culture and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
3
3
0
Order By: Relevance
“…In a recent study, fetal HC neurons immunopositive for vesicular glutamate transporter 1 (vGluT1) were observed to co-localize with ChAT (Bhargava et al, 2010 ), consistent with previous observations demonstrating glutamate and ACh co-release in some types of cholinergic neurons (Allen et al, 2006 ; Ren et al, 2011 ). However, ChAT immunoreactivity was absent from all but a small subpopulation of vGluT1-positive neonatal cells grown for 13 days in culture (Bhargava et al, 2010 ). Consistent with the idea that ChAT expression is downregulated in glutamatergic neurons, we found that a subset of CA3 SP neurons express ChAT-YFP (Figures 2A,F ) but do not exhibit ChAT immunoreactivity (Figures 5A–C, G–I ).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In a recent study, fetal HC neurons immunopositive for vesicular glutamate transporter 1 (vGluT1) were observed to co-localize with ChAT (Bhargava et al, 2010 ), consistent with previous observations demonstrating glutamate and ACh co-release in some types of cholinergic neurons (Allen et al, 2006 ; Ren et al, 2011 ). However, ChAT immunoreactivity was absent from all but a small subpopulation of vGluT1-positive neonatal cells grown for 13 days in culture (Bhargava et al, 2010 ). Consistent with the idea that ChAT expression is downregulated in glutamatergic neurons, we found that a subset of CA3 SP neurons express ChAT-YFP (Figures 2A,F ) but do not exhibit ChAT immunoreactivity (Figures 5A–C, G–I ).…”
Section: Discussionsupporting
confidence: 84%
“…What are the potential consequences of cholinergic modulation of ChAT-expressing neurons in the HC? Since ACh release from HC ChAT+ cells has not been definitively demonstrated, it remains an unresolved issue, but given the possible developmental downregulation of ChAT expression (Bhargava et al, 2010 ), ACh release from HC interneurons is likely to play a more prominent role during development than in the adult. Future studies investigating the expression of ChAT immunoreactivity during development of the HC are needed to clarify this issue.…”
Section: Discussionmentioning
confidence: 99%
“…The image ratio 197 Au/ 12 C 14 N showed a distinct localization of the nanobody in the neurite area. Particularly, the 197 Au signal localizes as "hot spots" along the neurites as expected for the distribution of vGlut in neurons [21,22] (Figure 2C). The line scan profiles across the "hot spot" in the neurites showed significant signal-to-noise of the 197 Au signal for the labeled structure (Figure 2B and 2D).…”
Section: Resultssupporting
confidence: 68%
“…The cell isolation procedures in this study were approved by Guide for the Care and Use of Laboratory Animals and in agreement with the Ethics Committee of The first affiliated hospital of Nanchang University. Neonatal rat hippocampal neuron was isolated as previously reported (Bhargava et al 2010). Briefly, 1~2 day-old neonatal Sprague-Dawley rats were sacrificed and the whole brains were collected.…”
Section: Neonatal Rat Hippocampal Neuron Isolation Culture and Transmentioning
confidence: 99%